2015
DOI: 10.1016/j.jdent.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Wall-lesion development in gaps: The role of the adhesive bonding material

Abstract: The presence and location of an adhesive bonding material in the composite-dentin gaps plays a role on the wall caries lesion development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…The presence of bonding material could act as a retention factor for biofilm growth, and this could explain the increase of secondary caries progression in this condition. Although the thickness of the biofilm was not measured, results from a recent in situ study performed by our group corroborate this [Montagner et al, 2015].…”
Section: Doi: 101159/000490195supporting
confidence: 59%
See 1 more Smart Citation
“…The presence of bonding material could act as a retention factor for biofilm growth, and this could explain the increase of secondary caries progression in this condition. Although the thickness of the biofilm was not measured, results from a recent in situ study performed by our group corroborate this [Montagner et al, 2015].…”
Section: Doi: 101159/000490195supporting
confidence: 59%
“…It has been demonstrated that CHX used as an MMP inhibitor in demineralized dentin after etching and prior adhesive procedures improves the hybrid layer integrity and bond strength between the tooth and the composite resin [Carrilho et al, 2007b;Montagner et al, 2015], but these results have not been confirmed in recent clinical trials [Gostemeyer and Schwendicke, 2016;Favetti et al, 2017]. It is speculated that MMPs remain inhibited for as long as CHX remains bonded to the collagenous matrix, but there is still no consensus about how long a CHX solution will retain its MMP inhibitory activity in a dentin substrate [Carrilho et al, 2007b].…”
Section: Discussionmentioning
confidence: 99%
“…However, this may raise some doubts on the comparability of samples placed in the upper and lower slots. Although we estimate this to be unlikely, also based on a separate analysis of composite samples in the upper and lower slots [Montagner et al, 2015], we cannot be completely certain. In subsequent studies, the sample distribution should also be randomized for upper and lower slot position.…”
Section: Discussionmentioning
confidence: 83%
“…The presence of these components in Clearfil SE Protect has been reported to prevent long-term deterioration of the adhesive interface to a greater extent than Clearfil SE Bond [20,32,33]. Recent studies have revealed Clearfil SE Protect inhibits mineral loss from the walls of the lesion [34]. Despite the excellent results described for this adhesive system, its performance can potentially be compromised if the air-drying is incomplete.…”
Section: Discussionmentioning
confidence: 99%